Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13018-020-01885-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risks for surgical site infection after closed tibial plateau fractures in adults treated by open reduction and internal fixation: a prospective study

Abstract: Background: Surgical site infection (SSI) was the most common complication of tibial plateau fracture after open reduction and internal fixation (ORIF). Severe infections even required repeat surgeries, which would cause serious psychological harm to patients and increased the economic burden of treatment. In order to identify the characteristics of the SSI and to avoid the occurrence of SSI, we conducted a prospective study to investigate the incidence and independent risk factors of SSI after ORIF for closed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 33 publications
1
16
1
1
Order By: Relevance
“…No significant differences were found between patients with and without infection regarding age, time between trauma and care, duration of external fixator, duration of surgery, or number of participants involved in the surgical procedure. This differs from findings reported in previous studies regarding the duration of fixator use and duration of surgery [ 2 , 7 , 13 ]. According to the literature, each additional hour of surgery increases the risk of surgical site infection in the postoperative period by approximately 78% [ 6 , 7 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…No significant differences were found between patients with and without infection regarding age, time between trauma and care, duration of external fixator, duration of surgery, or number of participants involved in the surgical procedure. This differs from findings reported in previous studies regarding the duration of fixator use and duration of surgery [ 2 , 7 , 13 ]. According to the literature, each additional hour of surgery increases the risk of surgical site infection in the postoperative period by approximately 78% [ 6 , 7 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In the analysis of potential risk factors for infection in patients with tibial plateau fracture, open fracture was the only variable that significantly increased the likelihood of infection in the immediate postoperative period (OR: 1.22; 95% CI: 0.93-1.62; p=0.012). This finding is in agreement with data reported in the literature [ 2 , 7 , 13 , 14 ]. It should be pointed out that, while open fracture contributes to the occurrence of infection, it cannot be controlled by the medical team.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Secondly, previous studies have mostly focused on a specific part. These parts have a high risk of postoperative infection, such as the tibia, ankle joint, and calcaneus [ 16 , 17 , 21 , 22 ]. Finally, due to the large number of variables in the clinical and microbial characteristics of the patients, we excluded medical records with missing data.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, AST levels in the SSI group were significantly higher than in the non-SSI group (23.5 versus 21.0 p = 0.038). Consistently, Li et al [15] demonstrated that AST is a risk factor for SSI after closed tibial plateau fractures. Fractures are widely acknowledged to be accompanied by soft tissue injury.…”
Section: Discussionmentioning
confidence: 69%